Identifying the aspects in employer branding of ksu putra mandiri to improve the employee engagement - Rosidi, A. Syafiq Andriansyah; Pritasari, Adita (Journal of Business and Management, 2020)
Abstract. Student's business organization transfers knowledge and skill related to business that will provide opportunities for the students to understand the business problems and solutions. This organization usually has a dynamic and flowing nature. Dynamic and flowing means the cadre or its management always changes from time to time. The data collected are from one business division of a students' business organization in the Bandung area, namely Kantin Barat Laut (KBL). KBL is one of Koperasi Kesejahteraan Mahasiswa Institut Teknologi Bandung (KOKESMA ITB) businesses. The dynamic and flowing nature causes miscommunication between management and employees, ex and current management, in employee’s perspective, they feel superior because they work longer, and in the manager’s perspective, they feel disinclined although their positions are higher. Miscommunication makes the company unable to achieve its goals effectively. The communication climate becomes an indicator for an organization to judge how well the interaction occurs between its members. A positive communication climate can make it easier for an organization to achieve its goals. The data collection used in this research are interviews, observation, and document review. The results show that employees tend to be closer to manager and president director because they are the authorities to make changes and developments.Keywords: Student's Business Organization, Fast Change Management, Communication Climate